Ieee Isr 2013 2013
DOI: 10.1109/isr.2013.6695715
|View full text |Cite
|
Sign up to set email alerts
|

Optimization-based motion retargeting integrating spatial and dynamic constraints for humanoid

Abstract: In this paper, we present an optimization based retargeting method for precise reproduction of captured human motions by a humanoid robot. We take into account two important aspects of retargeting simultaneously: spatial relationship and robot dynamics model. The former takes care of the spatial relationship between the body parts based on "interaction mesh" to follow the human motion in a natural manner, whereas the latter adapts the resulting motion in such a way that the dynamic constraints such as torque l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…(Safonova and Hodgins, 2007) combined interpolation and motion graphs. (Moulard et al, 2013) integrated spatial and dynamic constraints for humanoid character. (O'Brien et al, 2011) showed space-time vertex constraints to adapt the animation, the motion adaptation describes constraints of dynamics and kinetics.…”
Section: Related Workmentioning
confidence: 99%
“…(Safonova and Hodgins, 2007) combined interpolation and motion graphs. (Moulard et al, 2013) integrated spatial and dynamic constraints for humanoid character. (O'Brien et al, 2011) showed space-time vertex constraints to adapt the animation, the motion adaptation describes constraints of dynamics and kinetics.…”
Section: Related Workmentioning
confidence: 99%
“…5. The effect of approximating the nonlinear dynamic equation of torque to be linear, (7), can be seen more clearly when the limit is set to be stricter, for example, set to half the real limit as shown Red, blue, and black lines represent original data, generated data, and limit lines, respectively. X-axis is time and Y-axis is each value specified in each subfigure.…”
Section: Filteringmentioning
confidence: 99%
“…They seemed to focus more on objective functions. Moulard et al 7 relied also on box limits and further took ZMP into account. Perhaps the most advanced work that is close to the offline optimization part of our work is Khoury et al 8 They considered many physical limits similar to ref.…”
Section: Introductionmentioning
confidence: 99%
“…Deriving motions from a pre-segmented motion capture database [7] [11] also have been actively developed. To make robot motions look as much like original human motions as possible, optimization-based methods [12] [13] [14] have been developed. However their cost functions in optimization are fixed regardless of target tasks; There is no guarantee that those functions are essential for any other motions.…”
Section: Introductionmentioning
confidence: 99%